Harmonic Mappings of the Hexagasket to the Circle (Analysis in Theory and Applications, 2011)
Harmonic mappings from the hexagasket to the circle are described in terms of boundary values and topological data. Explicit formulas are also given for the energy of the mapping. We have generalized the results in [10].